Tingkat Literasi Mahasiswa Politik Islam UIN Raden Fatah Palembang Terhadap Kebijakan Omnibus Law - Pratama, Boma (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
Political Literacy Level is the level of a person's ability to process and understand information while doing the process of reading, writing, and understanding something. In the past, literacy was defined as the ability to read and write. Currently, the term Literacy has begun to be used in more meanings. This study aims to analyze how far the level of political literacy of Islamic politics study program students to the Omnibus Law policy. The sample used in this study were students of the 2017-2020 Islamic Politics study program who are still active at the Faculty of Adab and Humanities. The variable sought in this study is the level of student political literacy on the Omnibus Law policy.The sampling technique used is proportional sampling with predetermined criteria. A sample of 68 students was obtained from 4 batches of the Islamic Politics study program at the Faculty of Adab and Humanities. The data collection technique used is using questionnaires distributed in 4 different batches.The results showed that the level of political literacy of the students of the Islamic Politics Study Program towards the Omnibus Law policy was relatively high, this was evident from the results of the questionnaires that were randomly distributed in 4 different classes showing a high understanding. Keywords: Literacy Level, Politics, Students, Policy, Omnibus Law.